Toxicity and Reproductive Parameters Impairment of Cypermethrin in Male Guinea Pig (Cavia porcellus) - Bertin Narcisse Vemo; Augustave Kenfack; Ferdinand Ngoula; Edouard Akono Nantia; Claude Cedric Njieudeu Ngaleu; Arthénice Jemima Nounamo Guiekep; Astride Martine Megnimeza Tsambou; Ferry Nana Yidjeu; Chancel Patrick Nelo; Alexis Teguia (Turkish Journal of Agriculture: Food Science and Technology, 2018)
Cypermethrin is a large spectrum action insecticide, globally employed to control pests in agriculture and some human and domestic animals ectoparasites. This study aimed to evaluate its toxicity and reproduction impairment in male guinea pig. Forty adult male guinea pigs were divided into 4 groups and orally submitted to 0, 92, 137.5 and 275 mg/kg body weight/day for 90 days. The weight of the liver increased significantly, while that of kidneys decreased significantly in treated animals compared to controls. Serum concentrations of creatinine, urea, ALAT, ASAT, total cholesterol, prostatic acid phosphatase increased significantly, while the testicular total protein level decreased significantly in groups given the insecticide relatively to the control. The testes weight, libido, serum level of testosterone, mobility, sperm count and the percentage of spermatozoa with entire plasma membrane decreased significantly in animals exposed to cypermethrin with reference to controls. The percentages of abnormal spermatozoa increased significantly in animals submitted to 137.5 or 275 mg/kg body weight (bw) of cypermethrin compared to control ones. On the testis histological sections of pesticide-treated animals, immature germinal cells were observed in the lumen of seminiferous tubules. Cypermethrin was toxic in male guinea pig and damaged reproductive parameters.